Variational calculations of excited states with zero total angular momentum vibrational spectrum of H2 without use of the Born–Oppenheimer approximation - Bubin, Sergiy; Adamowicz, Ludwik (American Institute of Physics Publishing, 2003)
Very accurate, rigorous and fully variational, all-particle, non-Born–Oppenheimer calculations of the vibrational spectrum of the H2 molecule have been performed. Very high accuracy has been achieved by expanding the wave functions in terms of explicitly correlated Gaussian functions with preexponential powers of the internuclear distance. An indicator of the high accuracy of the calculations is the new upper bound for the H2 nonrelativistic nonadiabatic ground state energy equal to 21.164 025 030 0 hartree
Keywords: physics; non-Born–Oppenheimer calculations